Abnormal Abilities: Black Women and the Production of Able-Bodied Normalcy in Thylias Moss’s Slave Moth - Sarah L. Orsak (Disability Studies Quarterly, 2023)
This article offers an alternative genealogy for disability accounts of normalcy by analyzing American poet Thylias Moss’s 2004 neo-slave narrative in verse, Slave Moth. While disability scholars have historically understood normalcy and able-bodiedness as synonymous, ability is not always normative for Black women. Although Slave Moth’s narrator Varl is putatively able-minded, her enslaver positions her as abnormal because she is literate. Drawing on Black feminist thought, I argue that normalcy describes multiple, seemingly contradictory, measures that operate through racialized standards of proper capacity. Moss illuminates how Black women and girls might inhabit a position of abnormality-ability because she situates abnormality within chattel slavery, making freak shows peripheral to the narrative. The anti-black formation of abnormality-ability mediates the boundaries of ability/disability and normal/abnormal. I address how this occurs in disability scholarship. Research on normalcy and the freak show has argued for the importance of disability as an analytic by relying on blackness as a fungible site of meaning. Ultimately, able-bodiedness becomes normative for white subjects, and disability abnormal, through their frictional relationship to and reliance on Black women’s abnormality-ability. However, Varl illuminates, critiques, and refuses this weaponization of abnormality. Through her embroidery, Varl develops technologies for living in the fissures of both abnormality and able-bodiedness.